Canaries in the Code Mine: Precarity and the Future of Tech Work. - Luhr, Sigrid Willa (Contemporary Sociology, 2026)
The book *Canaries in the Code Mine: Precarity and the Future of Tech Work* examines the increasing job insecurity faced by software developers, a group often viewed as enjoying stable and lucrative employment. Based on interviews with 120 New York City software engineers, it highlights how precarity affects different demographic groups, including young white and Asian men, women, Black and Latine workers, and older employees, each encountering distinct challenges related to job stability, career advancement, and workplace inclusion. The author also explores the potential for unionization in the tech industry amid high turnover and employer resistance, arguing that despite diverse experiences, tech workers share common struggles. The book situates these findings within broader labor market shifts, noting the rise of contract-based work and the looming impact of AI automation on the future of tech employment.